Experiential Learning in Introducing Information Systems - Ahmad Alif, Kamal; Adrus, Mohamad Tazuddin; Chong, Chee Jiun; Tarmizi, Mohammad Shukri (UNIMAS Publisher, 2023)
Introducing new knowledge with certain depth such as “Information Systems” to pre-university level has always been challenging. Majority of the students came from pure sciences background, and there are some among them with IT sciences in SPM yet still have limited exposure to the ICT field. To tackle this issue, experiential learning was implemented. The students undergo a series of activities for them to experience the workflow of a System Analyst before facing the assessment for this learning unit. A System Analyst expertise and specialize in Information Systems building and designing.